THE EFFECTIVENESS OF COLCHICINE AND ORYZALIN ON POLYPLOIDY INDUCTION IN TEAK (Tectona grandis Linn. f.) IN VITRO - Fauzan, Yusuf Sigit A.; Supriyanto; Mulyono, Joko; Tajuddin, Teuku (Indonesian Journal of Forestry Research, 2024)
Indonesian government has launched a community plantation forests program that would be beneficial for remedying shortage in domestic demand for teak wood every year. This program needs to be supported by the availability of quality seeds resources and quality seedlings utilizing polyploid teak (Tectona grandis). Our study aimed to examine the effectiveness of colchicine and oryzalin to modify diploid into polyploid T. grandis based on growth response, morphological, anatomical and cytological alteration, as well as the acclimatization ability of polyploid plantlets. The materials used were aseptic lateral shoots consisting of nodal segments which were immersed in antimitotic agents at the concentration of 0, 15 and 30 μM for 5 days, then cultured on regeneration medium until the 8 weeks and followed by acclimatization. The results showed that colchicine at the concentration of 30 μM was the most effective to induce polyploidy of plantlets in the parameter of high growth rate, the length of internodes, the number of leaf plantlets and increase the leaf surface area and the significant chlorophyll index content compared to the control. Anatomical analysis of polyploid was characterized by increasing the leaf thickness, stomata size, decreased stomatal density and increased chloroplast content in guard cells. Based on cytological examination on polyploidy plantlet, there was an increased in the number of chromosomes in the cell nucleus. The acclimatization of polyploid successfully induced rooting and a 100% survival rate of grown plantlets. Polyploid seedlings were able to grow and well adapted to the new environment of acclimatization